Cabozantinib for HCC Treatment, From Clinical Back to Experimental Models - Deng, Shanshan; Solinas, Antonio; Calvisi, Diego F. (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is the fourth leading cause of cancer-related mortality worldwide. Patients with early-stage HCC can be treated successfully with surgical resection or liver transplantation. However, the usual late diagnosis of HCC precludes curative treatments, and systemic therapies are the only viable option for inoperable patients. Sorafenib, an orally available multikinase inhibitor, is a systemic therapy approved for treating patients with advanced HCC yet providing limited benefits. Consequently, new drugs have been developed to overcome sorafenib resistance and improve patients' prognoses. A new promising strategy is using c-MET inhibitors, such as cabozantinib, as activation of c-MET occurs in up to 40% of HCC patients. In particular, cabozantinib, in combination with the checkpoint inhibitor atezolizumab, is currently in phase 3 clinical trial for HCC, and the results are eagerly awaited. Herein, we summarize and review the drugs approved for the treatment of advanced HCC, mainly focusing on the clinical and preclinical efficacy evaluation of cabozantinib. Also, we report the available preclinical data on cabozantinib-based combination therapies for HCC, current obstacles for cabozantinib therapy, and the future directions for cabozantinib-based treatment for HCC.